PREVALENCE OF BRUCELLOSIS IN DAIRY COWS IN KRUCIL SUBDISTRICT, PROBOLINGGO REGENCY - Mufidah, Nisa; Riyadhi, Muhammad; Indasari, Elly Nur; Wulandari, Sri Helda (Buletin Veteriner Udayana, 2026)
Brucellosis is an important zoonotic infectious disease caused by bacteria belonging to the Brucella genus. Probolinggo Regency in East Java Province is recognized as one of the regions with a large population of dairy cattle, particularly in Krucil Subdistrict, which holds the highest number of dairy cows in the regency. This study aimed to assess the health status of dairy cattle related to Brucellosis infection in Krucil Subdistrict, Probolinggo Regency. The research employed a random sampling approach involving 35 Friesian Holstein (FH) dairy cows originating from three villages: Tambelang, Bermi, and Krucil. Serological testing was carried out at the BBVet Wates Laboratory using the Rose Bengal Test (RBT) method to identify antibodies against Brucella abortus. The results of the study showed that the prevalence of brucellosis in Krucil District was 0%. The findings indicated that all collected samples (100%) tested seronegative for Brucellosis, demonstrating that the area under study remains free from this disease. Ongoing preventive programs, including vaccination, disease monitoring, and the implementation of strict biosecurity, are recommended to preserve the Brucellosis-free status.